Cardiorespiratory Fitness and Highly Sensitive Cardiac Troponin Levels in a Preventive Medicine Cohort. Issue 12 (December 2016) - DeFina, Laura F.; Willis, Benjamin L.; Radford, Nina B.; Christenson, Robert H.; deFilippi, Christopher R.; de Lemos, James A.
Abstract : Background: Cardiorespiratory fitness (CRF) and highly sensitive cardiac troponin T (hs‐cTnT) are associated with risk of all‐cause and cardiovascular mortality as well as incident heart failure. A link of low CRF to subclinical cardiac injury may explain this association. We hypothesized that CRF would be inversely associated with hs‐cTnT measured in healthy adults over age 50. Methods and Results: We evaluated 2498 participants (24.7% female, mean age 58.7 years) from the Cooper Center Longitudinal Study between August 2008 and January 2012. Plasma specimens obtained shortly before CRF estimates by Balke treadmill testing were used for hs‐cTnT assays. CRF was grouped into low CRF (category 1), moderate CRF (categories 2–3), and high CRF (categories 4–5). Multivariable logistic regression was used to estimate the association of CRF with hs‐cTnT. The prevalence of measurable hs‐cTnT (≥3 ng/L) was 78.5%. In multivariable analyses, low‐fit individuals were significantly more likely than high‐fit individuals to have elevated hs‐cTnT (≥14 ng/L) (odds ratio 2.47, 95% CI 1.10–5.36). Conclusions: In healthy older adults, CRF is inversely associated with hs‐cTnT level adjusted for other risk factors. Prospective studies are needed to evaluate whether improving CRF is effective in preventing subclinical cardiac injury.